Complexation of fungal extracellular nucleic acids by host LL-37 peptide shapes neutrophil response to Candida albicans biofilm - Juszczak, Magdalena; Zawrotniak, Marcin; Rapala-Kozik, Maria (Frontiers in Immunology, 2024)
Candida albicans remains the predominant cause of fungal infections, where adhered microbial cells form biofilms - densely packed communities. The central feature of C. albicans biofilms is the production of an extracellular matrix (ECM) consisting of polymers and extracellular nucleic acids (eDNA, eRNA), which significantly impedes the infiltration of host cells. Neutrophils, as crucial players in the innate host defense, employ several mechanisms to eradicate the fungal infection, including NETosis, endocytosis, or the release of granules containing, among others, antimicrobial peptides (AMPs). The main representative of these is the positively charged peptide LL-37 formed from an inactive precursor (hCAP18). In addition to its antimicrobial functions, this peptide possesses a propensity to interact with negatively charged molecules, including nucleic acids. Our in vitro studies have demonstrated that LL-37 contacting with C. albicans nucleic acids, isolated from biofilm, are complexed by the peptide and its shorter derivatives, as confirmed by electrophoretic mobility shift assays. We indicated that the generation of the complexes induces discernible alterations in the neutrophil response to fungal nucleic acids compared to the effects of unconjugated molecules. Our analyses involving fluorescence microscopy, flow cytometry, and Western blotting revealed that stimulation of neutrophils with DNA:LL-37 or RNA:LL-37 complexes hamper the activation of pro-apoptotic caspases 3 and 7 and fosters increased activation of anti-apoptotic pathways mediated by the Mcl-1 protein. Furthermore, the formation of complexes elicits a dual effect on neutrophil immune response. Firstly, they facilitate increased nucleic acid uptake, as evidenced by microscopic observations, and enhance the pro-inflammatory response, promoting IL-8 production. Secondly, the complexes detection suppresses the production of reactive oxygen species and attenuates NETosis activation. In conclusion, these findings may imply that the neutrophil immune response shifts toward mobilizing the immune system as a whole, rather than inactivating the pathogen locally. Our findings shed new light on the intricate interplay between the constituents of the C. albicans biofilm and the host's immune response and indicate possible reasons for the elimination of NETosis from the arsenal of the neutrophil response during contact with the fungal biofilm.